Development of Kaya Slice (coconut jam slice): evaluation of physicochemical, sensory evaluation and macronutrients composition when cooperated with gelatin - H., Ab. Rahim; H., Ahmad; N., Wahab; M. H., Ab. Rahim (Rynnye Lyan Resources, 2022)
Kaya Slice is a nutritious traditional breakfast-on-the-go that was innovated from the traditional kaya. In this study, the traditional kaya was transformed into square shape gelatin to make it a more convenient and ready-to-eat breakfast. A total of six formulations were developed by using commercial and fresh coconut milk together with different percentages of gelatin (2%, 4%, and 6%). This insight was investigated by sensory evaluation using a 9-point hedonic and scoring test in descriptive data set. The best formulation obtained from the evaluation of 35 panellists was then characterized in terms of physicochemical properties (Texture Profile Analysis (firmness), Brix, Protein, Fat, Fiber, and Calories). From the descriptive data, all formulations were accepted by the panellist. Nevertheless, ANOVA analysis indicated that C2 (commercial coconut milk + 4% of gelatin) is the best formulation. In macronutrient analysis, Kaya Slice was found to have good dietary fibre content (0.11 g/100 g), high-fat content (0.49 g/100 g), protein content (0.32 g/100 g) compare to the commercial kaya (0.00 g/100 g), (1.00 g/100 g), and (0.00 g/100 g) respectively. Low-calorie content in Kaya Slice with 45 % of °Brix value is the minimal degree of Brix and the texture was softer (hardness) (significantly different (p<0.05)) to commercially processed cheese slice as standard. Overall, Kaya Slice has a great potential in becoming new emergent of traditional nutritious breakfast on the go.